Treatment of multiple drug-resistant tuberculosis (MDR-TB) in Iran. - Mirsaeidi, Seyed Mehdi; Tabarsi, Payam; Khoshnood, Kaveh; Pooramiri, Majid Valiollah; Rowhani-Rahbar, Ali; Mansoori, Seyed Davood; Masjedi, Heydar; Zahirifard, Soheyla; Mohammadi, Foroozan; Farnia, Parisa; Masjedi, Mohammad Reza; Velayati, Ali Akbar (International journal of infectious diseases : IJID : official publication of the International Society for Infectious Diseases, 2005)
Masih Daneshvari Hospital, Tehran, Iran, 2000-2002.
Keywords: Adolescent; Adult; Aged; Amikacin; Antitubercular Agents; Cycloserine; Drug Therapy, Combination; Female; Humans; Iran; Isoniazid; Male; Middle Aged; Ofloxacin; Treatment Outcome; Tuberculosis, Multidrug-Resistant